Metachronous appearance of second malignancies in medullary thyroid carcinoma (MTC) patients: A diagnostic challenge and brief review of the literature - Alevizaki, M.; Kyratzoglou, E.; Bamias, A.; Tzanela, M.; Dimopoulos, M.A.; Saltiki, K. (Endocrine, 2013)
Medullary thyroid carcinoma (MTC) is a rare tumour which frequently occurs in the context of the multiple endocrine neoplasia syndromes, where it coexists with other usually benign tumours. The clinical picture varies and distant metastases are frequently present at diagnosis. Calcitonin levels are elevated in the presence of metastatic disease. Two MTC cases are presented, which had elevated postoperative calcitonin levels. Imaging revealed lung lesions which were originally attributed to metastatic disease from the MTC. However, at follow-up, these cases presented unusual features. The rapid increase in the lung lesions and the development of hypercalcaemia in the first patient suggested a second unrelated tumour. Biopsy of the lung lesion was compatible with lung adenocarcinoma. In the second patient, the appearance of a liver mass, although calcitonin levels remained stable, led to biopsy of the lesion: this was negative for calcitonin and compatible with metastatic lung adenocarcinoma. These MTC cases show that further malignancies may coexist with MTC and may obscure the clinical picture and influence the therapeutic decisions, especially in the case of metastatic disease. Features such as unusual imaging characteristics and the development of hypercalcemia, never encountered in MTC outside the MEN2 syndromes, as well as 'disproportionately' low calcitonin levels, incompatible with extensive metastatic disease, were the factors that led to further work-up. Both the cases subsequently proved to carry an unsuspected second malignancy. It is crucial to discriminate the metastatic lesion attributed to MTC from another coexisting primary malignancy, because different therapeutic strategies are needed for each setting. © 2013 Springer Science+Business Media New York.
Keywords: Hypercalcemia of malignancy; Lung cancer and medullary thyroid carcinoma; Medullary thyroid carcinoma; Papillary thyroid carcinoma; Primary malignancies coexistence; Simultaneous primary cancers